(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2017)
Assessment of genetic diversity is essential for germplasm characterization, utilization and conservation. Genetic diversity of 31 Aus rice landraces of Bangladesh was assessed using 36 SSR (simple sequence repeats) markers. A total of 141 alleles were detectedand the number of alleles per locus ranged from two (RM1216, RM145, RM282, RM293, RM567and RM496) to 10 alleles (RM304), with an average of 3.92. The gene diversity varied from 0.06 (RM145) to 0.80 (RM304) with an average of 0.54 and the PIC values ranged from 0.06 (RM145) to 0.78 (RM304), with an average of 0.48.PIC value revealed that RM304 was the best marker for characterizing the studied Aus rice genotypes. The dendrogram from unweighted pair-group method with arithmetic average clustering of markers classified the genotypes into five major groups with a coefficient of 0.49. Two and three-dimensional graphical views of Principal Coordinate Analysis (PCA) revealed that the genotypes Hashikalmi, Chaina, Puitraaijang, Saithsail, Kuchmuch, Kalodhan, Ausdhan and Itcriewere found far away from the centroid of the cluster and can be selected as parents for further breeding programs.The results provided some useful implications for establishment of sovereignty of Bangladeshi rice gene pool. This information will provide maximum selection of diverse parents, background selection during backcross breeding programs and assist in broadening germplasm-based rice breeding programs in future.